Celebrating 20 Years of Open Access and Innovation at JMIR Publications - Eysenbach, Gunther (JMIR Publications, 2019)
In this 20th anniversary theme issue, we are celebrating how JMIR Publications, an innovative publisher deeply rooted in academia and created by scientists for scientists, pioneered the open access model, is advancing digital health research, is disrupting the scholarly publishing world, and is helping to empower patients. All this has been made possible by the disintermediating power of the internet. And we are not done innovating: Our new series of "superjournals," called JMIRx, will provide a glimpse into what we see as the future and end goal in scholarly publishing: open science. In this model, the vast majority of papers will be published on preprint servers first, with "overlay" journals then competing to peer review and publish peer-reviewed "versions of record" of the best papers.